Organisation change and African agricultural development? Eessais on cotton sector reforms and index-based insurances - (:unkn) unknown (My University, 2012)
The African agricultural sector has been neglected by development aid during the last fifty years. It has not undertaken a green revolution, as it happened in Asia. The continent has a great potential for agricultural production but yields and technology adoption are still very low. Moreover many recent threats to food security represent a challenge for future development in Africa. Demographic growth, increase in commodity prices and price volatility, land use pressure and climate change are probably the most latent threats. In such context, it is necessary to develop new patterns of development for African agriculture. Those patterns should draw the consequences from past policies, which either relied on large investments and in favouring a development of the same nature that the one observed in rich or emerging economies. It seems that improving institutions and the environment to foster the evolution of African agriculture would be more adapted than previous strategies that consist in applying the same methods employed in the past. Food security can be achieved by improving rural households' income. Those households is composed by a vast majority of smallholders, for which agricultural production is a major resource for living. The necessary transition for stimulating production in remote areas seem to rely on fostering technology adoption and improve incentives for investments that would increase the productivity or the value added to smallholder production. We study two major organisational changes that are the reforms of cotton sector market structure in sub-Saharan Africa and index-based insurances. In both cases the point is to look at the potential of every organisation choice, reduce vulnerability and its effect, in particular the poverty trap phenomenon. The final objective is improve long run yield by foster investments, in spite of the risks borne by farmers and the tied budget constraint, consequence of the absence of financial (especial
Keywords: African Research